Genetic diversity of shallots (Allium ascalonicum L.) from several locations in North Sumatra, Indonesia based on RAPD markers (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hasanah Y, Mawarni L, Hanu, H, Lestami A. 2022. Genetic diversity of shallots (Allium ascalonicum L.) from several locations in North Sumatra, Indonesia based on RAPD markers. Biodiversitas 23: 2405-2410. Shallot (Allium ascalonicum L.) is one of the leading horticultural and spice commodities in Indonesia. Assembling shallot varieties to get a good seed quality requires a high genetic diversity which can be analyzed using molecular markers. This study aims to identify the genetic diversity of shallots from several locations in North Sumatra, Indonesia based on Random Amplified Polymorphic DNA (RAPD) markers. This research was conducted at the Biotechnology Laboratory, Faculty of Agriculture, University of Sumatera Utara, Medan from September to October 2021. A total of 11 shallot varieties from several locations in North Sumatra were genetically analyzed based on RAPD markers with OPA-13, OPB-07, OPD-20, OPM-01 primers. The results showed that 11 shallot varieties originating from several locations in North Sumatra had a high genetic diversity with the presence of two main groups at a dissimilarity coefficient of 76%. These beneficial results can be used as a complement to morphological markers in the genetic study of shallots for breeders to decide what genotypes will be crossed to make new genetic combinations in the development of shallots. This study reports the success of the shallot varieties’ fingerprints using RAPD markers.